REINTERPRETASI PANCASILA: (Sebuah Dinamika Pemikiran dalam Relasi Agama dan Negara di Era Reformasi) - Muhammad Imadudin; Muhammad Anis (EL-ADABI : Jurnal Studi Islam, 2023)
Constitutional change and democratization in Indonesia have reopened dialectics and dynamics among religious, cultural and philosophical traditions in the country. Contemporary scholars tend to agree that Pancasila and democracy are compatible with Islam. The interpretation of Pancasila have been widely discussed by a number of contemporary Indonesian scholars. They use their own paradigms and methods in their interpretation of Pancasila. Some scholars urge for the formalization of sharia in a Pancasila state, while others develop the ideas of religious moderation in a Pancasila state. The smaller groups of scholars interpret Pancasila in the secularistic paradigm. This paper discusses the interpretation of Pancasila among Muslim intelligentsia and civil society organizations. It seeks the most relevant and coherent paradigm for interpreting Pancasila. Hence, this paper shall examine the three paradigms of the relation/dialectic of religion and state. This paper maps out the thoughts and models of interpretation of Pancasila, that are discussed by Muslim intelligentsia and civil society organizations. The assumption built at the beginning of this paper is that the symbiotic paradigm has relevance, coherence, and correspondence with the values of Pancasila itself. Therefore, this paper shall examine the assumptions mentioned above. This paper is based on a library research, and also a qualitative research. It is, therefore, a basic/philosophical research as well. The sources of research data in this paper are collected  from related documents and other related writings.